Analisis Pengaruh Budaya Organisasi, Gaya Kepemimpinan Transformasional Dan Motivasi Kerja Terhadap Kinerja Pegawai - Setiawati, Firda; Prahiawan, Wawan (Jurnal Manajemen dan Bisnis, 2024)
The aim of this research is to analyze Organizational Culture, Transformational Leadership Style and Work Motivation on Employee Performance. This research was conducted at the Housing, Settlement and Land Office of Pandeglang Regency using a literature study method from library sources in the form of journals based on specific topics of organizational culture, transformational leadership style, work motivation and employee performance. The results of the analysis show that: (1) Organizational Culture influences Employee Performance (2) Transformational Leadership Style influences Employee Performance (3) Work Motivation influences Employee Performance. Keywords: Organizational culture, Transformational Leadership, Work Motivation, Employee Performance.